Pemanfaatan Firah Dan Metode Resitasi Untuk Meningkatkan Hasil Belajar Pada Pelajaran Sejarah Indonesia Kelas X AP 2 SMKN 2 Palu Tahun Pelajaran 2017/2018 - Anilawa Anilawa (Universitas Negeri Makassar, 2021)
This study aims to provide an overview of the use of firah (Historical Films) and recitation methods to improve learning outcomes in Indonesian history lessons in class X AP 2 SMKN 2 Palu in the 2017/2018 school year, with classroom action research methods with 36 students as respondents. The results of the study found an increase in learning outcomes from cycle I to cycle II. on aspects of knowledge, attitudes and skills. In the aspect of knowledge in cycle 1, students still reached the KKM of 52.77% and an increase in learning outcomes to 99.99% then in the aspect of attitude 71.66% in cycle 1 increased in cycle II to 96.66%. The skill aspect has increased with good and very very good predicates